PROSES KREATIF KETERAMPILAN MEMBACA PADA ANAK USIA DINI - Marwany Marwany (Jurnal Penelitian Agama, 2018)
Abstract: The creative process of reading skills carried out by early childhood is done through five important stages: first, the creative process of pronouncing the symbol of language, at this stage children carry out verbal recitation activities obtained through the process of listening (verbal) and intensive imitation of people around children are intentional and have goals. Secondly, the creative process of understanding and reciting simple language symbols, at this stage after reciting then they understands and knows simple words or languages pronounced, so that they begin to understand the meaning of a language in a simple way. Third, the creative process of understanding the meaning of lexical language, at this stage, understanding the meaning of the language of early childhood is more comprehensive so that language is understood more and more. Fourth, the creative process of understanding simple information, this is where early childhood not only understands the meaning of language, but also at the level of understanding information in a language. Fifth, the creative process recognizes simple text of reading sources, and finally, the simple text then can be understood by children. Keywords: creative process, reading skills, and early childhood.